ANALISIS PELAYANAN TRANSAKSI PRODUK PEGADAIAN MENGGUNAKAN APLIKASI TRING! PADA PEGADAIAN SYARIAH AHMAD YANI JEMBER - Puput Dwi Wulandari; Lailatul Kiptiyah; Niki Kurniasari; Khairunnisa Musari (Universitas Muhammadiyah Sumatera Utara, 2026)
Digital transformation in Islamic financial institutions has encouraged PT Pegadaian, through its Pegadaian Syariah, to develop application-based transaction services to improve customer service quality. However, the effectiveness of digital service implementation remains challenged by digital literacy, technological readiness, and user acceptance. This study aims to analyze transaction services for Pegadaian products using the Tring! by Pegadaian application at Pegadaian Syariah Ahmad Yani Jember, focusing on the technical features, service quality, advantages, challenges, and strategies for improving digital services. This study employed a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving key informants, including branch managers, operational staff, and Tring! users selected purposively until data saturation was achieved. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the Tring! application improves transaction convenience, efficiency, and flexibility through integrated digital features. Nevertheless, several challenges remain, including limited digital literacy among elderly customers, device constraints, unstable internet connectivity, and technical issues. This study concludes that the success of digital services depends not only on technological quality but also on user readiness, digital assistance, and continuous improvement of system security.